GROWTH RATE OF THE WEDGE CLAM DONAX CUNEATUS AT MIRIYA BAY, RATNAGIRI - Talikhedkar, P M; Mane, U H; Nagabhushanam, R (Indian Journal of Fisheries, 2011)
Growth of commercially important bivalves from Indian waters wasstudied by Paul (1942) in Mytilus viridis and Ostrea madrasensis, Rao (1951)in Katelysia opima, Abraham (1953) in Meretrix casta, Gokhale et al (1954)in Pinctada pinctada, Nayar (1955) in Donax cuneatus, Rao and Nayar (1956)in O. madrasensis, Rao et al (1962) in Solen kempi, Narasimham (1968) inAnadara granosa, Durve (1970) in M. casta, and Mane (1973) in K. opima.